2000
DOI: 10.1021/la990018r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Self-Assembled Monolayers for Biosensor Applications

Abstract: Mixed monolayers of thiol-terminated poly(ethylene glycol) (PEG) and thioacetyl GM1 glycolipid on Au(111) were examined utilizing atomic force microscopy, infrared spectroscopy, and grazing incidence X-ray diffraction to determine the composition, structure, and morphology and to characterize the specific and nonspecific interactions with protein. These monolayer architectures are robust and are readily controlled to provide a network of receptor GM1 in the PEG-terminated matrix. However, we also find signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 51 publications
2
58
0
Order By: Relevance
“…Ducker et al (1992) demonstrated that the forces between colloid particles could be measured by attaching a colloid particle to the end of an AFM cantilever. In biological systems, this approach has been adapted to estimate bond strength between different biological molecules such as ligands and receptors (You & Yu, 1999), antigen antibody binding (Nyquist et al, 2000), receptor binding (Raiteri et al, 1999), and the molecular assembly of biomolecules (Kossek et al, 1998, Perrin et al, 1999.…”
Section: Contact Mode Afmmentioning
confidence: 99%
See 1 more Smart Citation
“…Ducker et al (1992) demonstrated that the forces between colloid particles could be measured by attaching a colloid particle to the end of an AFM cantilever. In biological systems, this approach has been adapted to estimate bond strength between different biological molecules such as ligands and receptors (You & Yu, 1999), antigen antibody binding (Nyquist et al, 2000), receptor binding (Raiteri et al, 1999), and the molecular assembly of biomolecules (Kossek et al, 1998, Perrin et al, 1999.…”
Section: Contact Mode Afmmentioning
confidence: 99%
“…Gold is a useful film because a broad spectrum of groups can be attached to gold via thiol linkages. Thiols are well known to adsorb under mild conditions onto gold surfaces (Biebuyck & Whitesides, 1994;Fritz et al, 1996;Liu et al, 1994, Nyquist et al, 2000 and thiol adsorption is strong enough to use sugar-thiols as sensors, for these reasons we chose to use gold-coated tips.…”
Section: Sensor Designmentioning
confidence: 99%
“…Over the past two decades, self assembled monolayers (SAMs) (Love et al, 2005;Smith et al, 2004;Ulman, 1996) have been extensively studied due to their many applications in various fields such as electrochemistry (Eckerman et al, 2010), biosensors (Nyquist et al, 2000), protein separation (Chun and Stroeve, 2002) and enantiomer separation (Mastai, 2009). SAMs are organic assemblies formed by the adsorption of molecules from solution or from the gas phase onto the surfaces of solids.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of such phenomena as adsorption, critical nuclei formation and film growth gives us key understanding of important processes in biomaterials, biosensors, biotechnology and nanotechnology [2].…”
Section: Introductionmentioning
confidence: 99%